Challenges in the pathological diagnosis of erythropoietic protoporphyria: a case report - Yang, Tingting; Chen, Changxian; Li, Chunming; Wang, Jinjing (Frontiers in Medicine, 2025)
BackgroundErythropoietic protoporphyria (EPP) is a rare autosomal recessive disorder caused by mutations in the FECH gene, leading to ferrochelatase deficiency and the accumulation of protoporphyrin in various organs. EPP patients with liver damage have atypical histopathological manifestations, which pose challenges for pathological diagnosis.ContentWe report a 29-year-old male with recurrent abdominal pain and scleral jaundice. Initial liver dysfunction suggested autoimmune hepatitis, but liver biopsy revealed dense brownish granular deposits with red birefringence under polarized light, characteristic of EPP. Genetic testing identified a new mutation site (c.804 + 1del), which may be related to the disease. Additionally, the patient also has Gilbert’s syndrome.ConclusionThis case highlights the diagnostic challenges of EPP and the importance of integrating clinical history, histopathology, and genetic testing. Polarized light microscopy is crucial for identifying the characteristic features of EPP. Early genetic testing can guide timely diagnosis and treatment, contributing to the understanding of this rare condition.